O surround e a espacialidade sonora no cinema - Nelio Jose Batista Costa (2004)
This work describes the multichannel sound formats currently being used in cinema. It also analyses the advances introduced by sound digitalization and the application of new multichannel technologies on different media such as DVD, Television, Music, and the Internet. This work focus on the description of the formats and technologies used in surround sound on films, analysing its technical characteristics and singularities.